Decolonizing English Language Textbook Design in India - Mahapatra, S. (University of Jaffna, 2025)
Literary texts have historically dominated English language textbooks and the corresponding pedagogy in India. This practice, which involves teaching English as a subject (rather than a language), can be traced back to the British colonial period when including literary texts seemed to have a hidden agenda. They were subtly used to valorise a British knowledge system, promote British culture, maintain social control, legitimise colonialism, and, to some extent, support Christian missionary activities. As more Indian elites who led political movements received English education, the inclusion of literary texts was normalised. The practice continued after the independence as almost all the universities had English departments, and their faculty members, who often specialised in literary studies, determined the English language education policies in the country. While the policy may suit students who have exposure to English outside the classroom, it ignores the specific language needs of students from socioculturally disadvantaged backgrounds, who make the vast majority of Indian learners, especially in rural areas, with very little exposure to English in their non-academic social surroundings. Students from such disadvantaged backgrounds often struggle to cope with the linguistic demand to understand and process literary texts. Although it has been proved that employing authentic contexts and skill-focused approaches can accelerate language learning, English language textbook designing in India, especially at the school level, ignores empirical evidence regarding the acceptable challenge of vocabulary in texts and remains enmeshed in a colonial legacy. Ramifications of the textbook design trend have profound social justice implications. However, very little attention has been paid to the issue in applied linguistics research. In light of the background mentioned above, the proposed study aims to make a case for decolonising textbook design in India by adopting an empirically driven and socioculturally informed approach. To achieve this goal, first, a historical analysis of the English language textbooks in schools from the first half of the 19th century to modern times is undertaken to identify the patterns of literary text use. Then, a brief review of empirical studies indicating the impact of real-life context use on students’ language skills and abilities is conducted. In the next stage, the review outcomes are used to show how including literary texts does not serve the intended purpose of effectively equipping students from various socioeconomic backgrounds with English language skills. Last, an English language textbook decolonisation framework with a theoretical and an implementation part is proposed. Theories of second/foreign language learning, equity, inclusivity, and social justice drive the theoretical part of the framework. The implementation of the framework comprises a plan for changing the textbook design policy, raising awareness about social justice by including application-oriented content and collecting empirical evidence to strengthen the process of textbook design in the country.
Keywords: Textbook design; Social justice; India; Decolonisation; Framework